Sztuka, miłość i medycyna: Anna Bilińska-Bohdanowiczowa (1857–1893) w świetle wspomnień męża - Tomalska, Joanna (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2012)
Despite the fact, that Anna Bilińska-Bohdanowiczowa is one of the most interesting Polish female artists, as of yet no monograph was written about her. Three of her paintings for years have been housed in Muzeum Podlaskie in Białystok. The content of the article focuses on introducing the untimely demised painter through her husbands’—Antoni Bohdanowicz— memoirs published many years after her death.